Effects of Long-Run Demographic Changes in a Multi-Country Model - Masson, Paul (IMF Working Papers; Working Paper ;, 1991)
The macroeconomic effects of population aging are explored using data for the G-7 countries and Australia. The link between changes in birth and mortality rates on the one hand, and dependency ratios on the other, is first discussed, then empirical evidence on the effects of dependency ratios on net foreign asset positions and on consumption is presented. Simulations of changes in dependency ratios are then reported, using demographic projections to the year 2025. Finally, the plausibility of the implied changes in net foreign asset positions is discussed.